Arquiteturas E/E automotivas centralizadas - Costa, Alysson Percicotty da (2021)
The complexity increasing of software in contemporary cars rule new trends in electrical electronic (E/E) automotive architectures. As a result, a lot of model equipment manufacturers (OEMs) and suppliers have defended centralized E/E architectures as the automotive architectures of the future. In this work, we defend centralized E/E architectures application in automotive industry. We discuss the motivation for centralized architectural schemes by carefully examining the challenges of traditional decentralized automotive E/E architectures, while we evidence the comparable benefits offered by centralization. Next, the technologies needed to be used for new centralized architectures. Presenting the actual scenario of networking, virtualization, electronic control unit hardware and AUTOSAR classic and adaptive technologies, and discuss the state of adoption of these technologies in the industry. Throughout, functional safety is considered and addressed as a pervasive concern in the automotive industry.